ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK KENDARAAN BERMOTOR TERHADAP PENERIMAAN PENDAPATAN ASLI DAERAH DI PROVINSI KALIMANTAN BARAT - Fransius Napitupulu; Ariefanda Iqbal Perdana; Sari Rusmita (ITB AAS INDONESIA, 2024)
As one of the provinces in Indonesia, West Kalimantan is one of the provinces that depends on PKB as a contributor to local revenue. However, not much research has been done on the effectiveness and contribution of PKB to local revenue in Kalimantan.The purpose of this study is to enable local governments to make better decisions on how to manage local revenue sources. This analysis can also help increase public awareness of the role of PKB as a source of local revenue.The focus of this study is motor vehicle tax (PKB), and how PKB revenue impacts on West Kalimantan Province's local revenue. Quantitative descriptive research collects and analyzes numerical data. the average PKB revenue in 2021-2022 is 98.83% with a fairly effective category and PKB revenue in West Kalimantan Province in 2021-2022 is included in the medium criteria with an average contribution rate of 22.78%. not in accordance with the target that has been set. because many people are still affected by the COVID-19 pandemic, but the West Kalimantan provincial government can still manage motor vehicle taxes